2008
DOI: 10.2147/vhrm.s3995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the vasodilatory action of testosterone in the human pulmonary circulation

Abstract: Aim:To assess for the first time the vasodilatory effect of testosterone in the human pulmonary circulation utilizing both isolated human pulmonary arteries and isolated perfused human lungs. In addition, a secondary aim was to determine whether there was any difference in the response to testosterone dependant upon gender.Methods:Isolated human pulmonary arteries were studied by wire myography. Vessels were preconstricted with U46619 (1 nM–1 μM) prior to exposing them to either testosterone (1 nM–100 μM) or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…The co‐IP study confirmed the existence of a multiprotein complex formed by an interaction between hsp90, CSE and NR3C4. Furthermore, in line with the current literature, T decreased hsp90/NR3C4 binding (Falkenstein et al ., ; Smith et al ., ). These results provide novel information about the intracellular localization of CSE and its interaction with hsp90 and NR3C4, which is an essential requirement for testosterone‐induced increase in H 2 S production.…”
Section: Discussionmentioning
confidence: 98%
“…The co‐IP study confirmed the existence of a multiprotein complex formed by an interaction between hsp90, CSE and NR3C4. Furthermore, in line with the current literature, T decreased hsp90/NR3C4 binding (Falkenstein et al ., ; Smith et al ., ). These results provide novel information about the intracellular localization of CSE and its interaction with hsp90 and NR3C4, which is an essential requirement for testosterone‐induced increase in H 2 S production.…”
Section: Discussionmentioning
confidence: 98%
“…Testosterone induces vasodilation in the isolated rat pulmonary vasculature most likely via calcium antagonistic effects (131), and it has been confirmed that in isolated human pulmonary arteries, these vasodilatory effects are independent of gender (132). In rodents, testosterone is an even more potent pulmonary vasodilator than estradiol (133).…”
Section: The Effects Of Progestins and Androgens In Experimental Pahmentioning
confidence: 93%
“…Testosterone is also a potent vasodilator in isolated human pulmonary vasculature, an effect that is independent of gender (Smith et al ., ; Rowell et al ., ). It is in fact a more potent vasodilator than oestrogen in this vascular bed (English et al ., ).…”
Section: Androgens and Pahmentioning
confidence: 98%